Using gEUD based plan analysis method to evaluate proton vs. photon plans for lung cancer radiation therapy. (13th February 2018) - Xiao, Zhiyan; Zou, Wei J; Chen, Ting; Yue, Ning J; Jabbour, Salma K; Parikh, Rahul; Zhang, Miao
Abstract: The goal of this study was to exam the efficacy of current DVH based clinical guidelines draw from photon experience for lung cancer radiation therapy on proton therapy. Comparison proton plans and IMRT plans were generated for 10 lung patients treated in our proton facility. A gEUD based plan evaluation method was developed for plan evaluation. This evaluation method used normal lung gEUD(a) curve in which the model parameter "a" was sampled from the literature reported value. For all patients, the proton plans delivered lower normal lung V5 Gy with similar V20 Gy and similar target coverage. Based on current clinical guidelines, proton plans were ranked superior to IMRT plans for all 10 patients. However, the proton and IMRT normal lung gEUD(a) curves crossed for 8 patients within the tested range of "a", which means there was a possibility that proton plan would be worse than IMRT plan for lung sparing. A concept of deficiency index (DI) was introduced to quantify the probability of proton plans doing worse than IMRT plans. By applying threshold on DI, four patients' proton plan was ranked inferior to the IMRT plan. Meanwhile if a threshold to the location of curve crossing was applied, 6 patients' proton plan was ranked inferior to the IMRT plan. The contradictory ranking results between the current clinical guidelines and the gEUD(a) curve analysis demonstrated there is potential pitfalls by applying photon experience directly to the proton world. A comprehensive plan evaluation based on radio‐biological models should be carried out to decide if a lung patient would really be benefit from proton therapy.